Analyzing the Factors Affecting Profit Distribution on Islamic Banking - Popon Siti Maryam (Jurnal Ilmiah Ekonomi Islam, 2022)
This research aims to analyze the internal and external factors that have a significant effect on Islamic bank profit distributions so that it can inform the formulation of Islamic bank strategies. The analytical method used is panel data regression. The selected model is Fixed Effect Model, then tested by t-test and f-test. All independent variables in the study simultaneously affect the dependent variable. Partially, there are internal factors that have a significant effect on the profit sharing, namely Main Operating Revenue (POU), Earning Asset based on Collectability (KAP), Financing to Deposit Ratio (FDR), Net Return (NI), Return on Equity (ROE), and the ratio of Operating Expenses to Operating Revenue (BOPO), while internal factors that do not have a significant influence are Depositor Funds (DPK) and Return on Assets (ROA). The external factors that have a significant influence are the conventional bank's 3-month deposit interest rate and inflation, while the external factor of BI rate does not have a significant influence on the profit-sharing of customers.